Sciatic Nerve Block for Lower Limb Surgery in elderly patients - Laiq, Nasreen; Khan, Muhammad Naeem; Khan, Shahid; Jan, Akbar Said (Journal of Postgraduate Medical Institute, 2011)
To evaluate the effectiveness of regional anaesthesia and haemodynamic stability of sciatic nerve block for lower limb surgery in elderly patients. A prospective study of fifty patients was carried out at department of anaesthesiology of HMC, Peshawar and PIMS islamabad from may 2003 to April 2004. Sciatic nerve block was performed using the posterior approach of Labat. After identification of sciatic nerve, 20ml of 0.5% bupivacaine was injected through 22G spinal needle. effectiveness of sciatic nerve block was assessed by degree of sympathetic, sensory and motor blockaade below knee. Patients were monitored haemodynamically at five minutes interval throughout the procedure. Sciatic nerve block provides good anaesthesia and haemodynamic stability during lower limb surgery and prolong analgesia during postoperative period. hence it is a good laternative for general anaesthesia.